Role of Cystatin C as Early Predictor of Renal Dysfunction in Iron Overloaded Beta Thalassemia Major Patients (Advances in Applied Biological Research, 2026)
Background: Beta thalassemia major patients are at risk to developing renal dysfunction over a period of time, secondary to chronic anemia, iron overload and chelation therapy. Early observation of renal insufficiency is necessary for intervention. Objectives: The objective of this study was to assess the value of cystatin c as an early marker of renal dysfunction in pediatric patients with iron overload Beta thalassemia major and investigates the related clinical factors. Patients and Methods: This was a cross sectional study which was conducted in Babylon center for hereditary blood disorders in Babylon governorate, 74 patients with beta thalassemia major whose parents accepted to participate in this study. Data collection was done by direct interview with parents. It was done by using performed questionnaire and tested for epidemiological and clinical factors. The concentration of cystatin C, creatinine, ferritin and haemoglobin were determined. Apparent correlations with cystatin C were analyzed for several factors, including age, age at presentation, duration of the disease, age at first blood transfusion and compliance with therapy and then take blood sample and examine the patient height.Results: A total of 74 patients with beta thalassemia major were enrolled in this study. Cystatin C adjusted concentrations showed a trend to increase with the later age at diagnosis (P < 0.0001); patients with diagnosis by 3-5 years were found the highest (1.42 ± 0.230 mg/L) compared to those diagnosed earlier at < 1 year (1.08 ± 0.248 mg/L) or between 1-3 years (1.11 ± 0.201 mg/L). Age at the first blood transfusion (P = 0.001) and therapy adherence (P = 0.032) were significantly associated with cystatin C levels and were higher in the non adherence group. Correlation of cystatin C was statistically in significant with serum creatinine (P = 0.047) while no correlation with age (P = 0.476) and duration of disease (P = 0.7) was observed unlike creatinine. There was significant correlation between cystatin C and serum ferritin.There was cut-off point of 1.34 mg/L serves as a critical warning sign, prompting further investigation and potentially earlier initiation of nephroprotective measures. Conclusion: Cystatin C proved to be a more sensitive biomarker than serum creatinine for the early detection of renal dysfunction in iron-overloaded β-thalassemia major patients. The study demonstrated that Cystatin C levels were significantly elevated in these patients, even before conventional markers such as serum creatinine showed abnormalities. This indicates that Cystatin C can play an essential role in the early prediction and monitoring of renal impairment, allowing for timely interventions to prevent progression, Additionally, demographic factors such as age and duration of blood transfusion therapy were found to influence renal function deterioration, highlighting the need for continuous monitoring in high-risk groups.
Keywords: cystatin c, Epidemiological and clinical factors, investigation, β-thalassemia